Implementasi Budaya Sekolah dalam Meningkatkan Karakter Peserta Didik di mts. Mazra’atul Ulum Paciran - yogatama, pradita alvin (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the role of school culture in shaping the character of students at MTs. Mazra’atul Ulum Paciran, with a focus on the integration of character values ​​in social studies learning. Through a descriptive qualitative approach, data was obtained that the implementation of school culture such as the 3S habits (smile, greet, say hello), 5K (cleanliness, discipline, health, beauty, and politeness), and structured religious activities, are able to form a conducive learning environment that is full of moral values. Teachers act as the main agents in conveying character values ​​through role models, empathetic communication, and the use of contextual learning methods. Students demonstrate a cooperative attitude, high enthusiasm for learning, and active involvement in various activities that support character formation. These findings confirm that the synergy between school culture, the role of teachers, and student participation is the key to creating holistic and meaningful learning. A well-internalized school culture can be an effective means of instilling character values ​​sustainably.